Analysis of The Impact of Zakat Distribution Policy on Economic Growth in The Cileungsi Community - Muhammad Amirul Huda; Muhammad Aldo Rizky; Muhibban (Values: Jurnal Kajian Islam Multidisiplin, 2025)
This research aims to deeply analyze the impact of zakat distribution policy on the economic growth of Ciliengsi community. Using a qualitative approach, this r esearch explores the experiences and perceptions of zakat recipients, zakat givers, and managers of zakat institutions. Information was collected through in-depth interviews and participatory observation. The results show that zakat not only provides financial assistance, but also has significant social impacts, such as increased work motivation, business development, and strengthening social networks. However, this study also identified some challenges in the implementation of zakat distribution policy, such as the lack of transparency and capacity of zakat institutions. This study concludes that zakat has great potential as an instrument to promote economic growth and reduce inequality. To achieve this potential, more systematic and integrated efforts are needed in the management and distribution of zakat